Stephane Jasmin, Jerry DeBerry, Cynthia Wong, Valerie Norris, and Danita Tankersly (Tufts Archival Research Center, 2017)
Stephane Jasmin, Jerry DeBerry, Cynthia Wong, Valerie Norris, and Danita Tankersly on College Avenue